A prospective randomized double blind study to compare dexmedetomidine and midazolam in ear nose and throat surgery for monitored anesthesia care - Delmade, Manmath A.; Parikh, Devangi A. (International Journal of Research in Medical Sciences, 2017)
Background: Analgesia and sedation are usually required for the comfort of the patient during ear, nose and throat surgery done under local anesthesia as a part of monitored anesthesia care (MAC). In this study, patients satisfaction scores and effectiveness of sedation and analgesia with dexmedetomidine were compared with midazolam. Methods: Thirty patients received intravenous dexmedetomidine 1µg/kg bolus for 10 minutes followed by continuous infusion at 0.5 µg/kg/hr (group D). Thirty patients received intravenous midazolam 40 µg/kg bolus for 10 minutes followed by infusion at 50 µg/kg/hr (group M). Intravenous fentanyl (2ug/kg) was administered in both the groups. Vital parameters such as heart rate, mean blood pressure (MBP), respiratory rate (RR), SpO2, ramsay sedation score (RSS) and visual analog scale (VAS) was observed and recorded throughout the operation and then three times in the recovery room i.e. at arrival 30 and 60 min. After achieving RSS = 3, local infiltration at surgical site was given. Results: The drop in HR and MBP from pre-operative value was observed at various intervals during the surgery and also in the recovery in both the groups but it was significant in group D (P<0.005). Patient satisfaction was significantly better with dexmedetomidine compared to midazolam (p=0.0001). There were no side effects in both of the groups except for bradycardia in group D which was reversed easily with injection atropine. Conclusions: Dexmedetomidine promises to be a suitable alternative to midazolam with added advantage of better patient satisfaction and faster recovery, but with close monitoring of hemodynamics.